Effects of lactation feed intake and creep feeding on sow and piglet performance - R C Sulabo; J Y Jacela; E J Wiedemann; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
A total of 84 sows (PIC, Line 1050) and their litters were used to determine the effects of lactation and creep feeding on sow and piglet performance. Three groups of sows were blocked according to day of farrowing and parity and allotted to four treatments in a 2 × 2 factorial with lactation feed intake (ad libitum vs. restricted) and creep feeding (none vs. creep) as factors. Piglets were cross-fostered within each block to standardize litter weights and litter size (>11 pigs). A common lactation diet (1,586 kcal ME/lb, 0.97% TID Lys) was used in the study. From d 3 of lactation, ad libitum sows were allowed free access to feed while restricted sows were fed 25% less than those fed ad libitum. A pelleted creep diet (1,585 ME/lb, 1.56% TID Lys) with 1.0% chromium oxide was offered to creep-fed pigs from d 3 to weaning (d 21). Piglets were weighed individually at d 3, 7, 14, and 21. Amount of creep feed consumed was determined daily. Fecal samples from all creep-fed pigs were taken on d 7, 14, and 21 and fecal color was assessed to categorize pigs as eaters or non-eaters. Sow weight and P2 backfat thickness (6.5 cm from the midline over the last rib) were measured after farrowing and at weaning. There was no interaction between lactation feed intake and creep feeding. Ad libitum feeding of sows reduced BW loss (-33.0 vs. -52.9 lb; P<0.01), improved total (P<0.04) and daily (P<0.04) gains of litters, and increased (90 vs. 71%; P<0.03) the percentage of sows returning to estrus by d 14 compared with limit-fed sows. Creep feeding did not affect (P>0.30) sow BW and backfat loss, but increased days to estrus (5.4 vs. 4.9 d; P<0.03) for sows that returned to heat by 14 d. Creep feeding tended to improve litter weaning weights (132.7 vs. 124.9 lb/d; P<0.09) by reducing mortality rate after cross-fostering (3.9 vs. 7.3%; P<0.06). Total creep feed intake of litters did not differ (2.24 vs. 2.28 lb/litter; P<0.93) between ad libitum and limit-fed sows. About 60% of the creep-fed pigs were categorized as eaters. Of those identified as eaters, 23, 20, and 57% began consuming creep feeding from d 3 to 7, 7 to 14, and 14 to 21, respectively. From d 0 to 28 post-weaning, there was no effect of creep feeding on d 28 weights (P<0.93), ADG (P<0.86), ADFI (P<0.93), and F/G (P<0.95) compared to non-creep fed pigs. Eaters tended to be heavier until d 28 post-weaning (P<0.16) and had greater (P<0.06) ADG and total gains than non-eaters and no creep pigs. In conclusion, creep feeding improved survivability, but had no effects on pre-weaning gain and sow performance. Low feed intake during lactation negatively affected both sow and litter performance. Creating more eaters in whole litters may be beneficial in improving post-weaning performance.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Creep feeding; Feed management; Lactation